Leveraging Green Dynamic Capabilities in Developing Green Marketing Strategies to Explain Green Competitive Advantage - Karsam Karsam; Solihin Solihin; Nadiah Binti Abdul Hamid (Institut Bisnis dan Informatika Kesatuan, 2025)
Objective - In order to determine how a company's green dynamic capabilities interact with green marketing strategies to affect the degree of green competitive advantage in Indonesia's tourism and hospitality sector, this study looks at the resource-based view and dynamic capabilities theory in the context of the industry. Design/methodology/approach - Using multi-source data and three-wave time data from 322 respondents in the tourism industry to test the hypothesis. Findings - The study's findings show that all of the assumptions were supported, demonstrating the direct and indirect connections between green competitive advantage, green marketing tactics, and green dynamic capabilities. - For practitioners and policymakers looking to improve the competitive edge and sustainability performance of businesses in the quickly expanding tourist industry, this study provides insightful information.